O-Juzu Dalam Praktik Ritual Buddha Nichiren - Mirrah Megha Singamurti; Kabul Praptiyono (Religi: Jurnal Studi Agama-agama, 2021)
This study aims to describe the symbolic meaning of O-Juzu in the Buddhist view of Nichiren. O-Juzu became one of the attributes for performing nichiren Buddhist rituals. In terms of its shape, O-Juzu is the same as the prayer beads used by other religious people. However, O-Juzu, whose distinctive bead with a total of 108 items, became the researcher's interest in analyzing philosophically from the perspective of Nichiren Buddha. This research uses descriptive qualitative approaches and library research methods. Data collection in this study uses documentation in the form of books, journals, and other scientific articles. Miles and Huberman data analysis models researchers use to perform data validity.The most basic ritual practice of Nichiren Buddhism is called gongyo. In doing gongyo, the Nichiren Buddhists read the books of Hoben (second chapter) and Juryo (sixteenth chapter) of the Lotus Sutra. Nichiren Buddhists need the most essential religious attributes consisting of butsudan (altar) and O-juzu (beaded beads). The use of O-juzu in gongyo practice by rotating it once, forming the number eight. The end of the number eight with three strands is placed above the middle finger of the right hand, and the end with two strands above the left middle finger. Short strands are located on the outside of the hand held together with the palms and fingers touching. In using O-Juzu done with Nam which has the meaning of making the inheritance of the highest law for each individual by combining it in practice of life with the six senses used for the fusion of practice with the pronunciation of "Myoho-Renge-Kyo" where all that we see as ordinary human beings is visible from the impurities of the Nine realms and in turn seen from the glory of being a Buddha in the world of ten.